Sistem Informasi Manajemen Pada Kantor Perusahaan Listrik Negara Kota Palu - Sadik, Ahmad; Riadi, Slamet; Salingkat, Syarif Permana (JPS: Journal of Publicness Studies, 2024)
This study aims to determine how the management information sistem at the hammer city state electricity company office provides information on electricity outages and scheduling. The theory used in this research is Azhar Susanto (2013) which consists of 4 important elements in information sistem services, namely: accurate, relevant, timely and complete. The informants in this study were 6 (six) people. The method used is Descriptive Qualitative. Data collection techniques in this study using observation, interviews, and documentation techniques. The results of this study indicate that the management information sistem at the Palu City State Electricity Company Office in providing information on power outages is quite good, however, there are still problems with the accuracy and timeliness of the distribution of the power outage schedule. In the accurate aspect, there is a problem, namely the duration of the power outage that is not in accordance with the schedule that has been distributed by PLN Palu City and there is a delay in power outages that are not in accordance with the distributed schedule, then the timely aspect of the information on the schedule of power outages in the Palu City area is not running well. This can be seen from the applicable Standard Operating Procedure (SOP), namely the blackout schedule which should be distributed one week or at least three days before the blackout. However, in reality, there are still frequent power outages without any information.